Health Care Workers’ Attitudes Towards Social Robots. Some Empirical Evidence - Carradore, Marco; Bertuzzi, Elena; Bonito, Naomi; Trivellato, Francesca (Italian Sociological Review, 2023)
The application of social robots is spreading to many different areas of daily life. They are being used for tasks such as health monitoring, caregiving assistance and educational activities. The use of robots has sociological implications due to the fact that some nations are facing challenges associated with ageing populations and a shortage of workers in certain sectors, including healthcare. Social robots are being considered as one way of addressing these challenges. Understanding the extent to which workers accept the use of social robots is important for social research. The aim of this paper was to identify the sociodemographic and work-related factors that influence health care workers’ attitudes towards social robots. A non-representative sample of 302 health care workers was analysed. The General Attitudes Towards Robots Scale (GAToRS) was used to measure attitudes towards social robots. The results show that although the topic of robotics has become familiar to health care workers and they generally express positive views about them, most have not had much personal experience of their use. Additionally, health care workers expressed a high level of interest in the scientific discoveries and technological developments of social robots, and this could contribute to developing acceptance among these professionals regarding their use.